2020
DOI: 10.3390/ijms21228867
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Novel Circular RNAs Deriving from BCL2L12 and Investigation of Their Potential Value as a Molecular Signature in Colorectal Cancer

Abstract: The utility of circular RNAs (circRNAs) as molecular biomarkers has recently emerged. However, only a handful of them have already been studied in colorectal cancer (CRC). The purpose of this study was to identify new circRNAs deriving from BCL2L12, a member of the BCL2 apoptosis-related family, and investigate their potential as biomarkers in CRC. Total RNA extracts from CRC cell lines and tissue samples were reversely transcribed. By combining PCR with divergent primers and nested PCR followed by Sanger sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…Numerous evidence supports that circRNAs are correlated with the progression of human diseases through their interaction with signaling pathways, and their biomarker potential has been proved by multiple studies [ 16 , 17 ]. In particular, circRNAs are generally proven to intervene in tumor stemness, migration, invasion, and metastasis [ 18 ]; for instance, they are involved in the activation of the epithelial–mesenchymal transition (EMT) process via the WNT/β-catenin signaling pathway, affecting directly the tumor progression [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous evidence supports that circRNAs are correlated with the progression of human diseases through their interaction with signaling pathways, and their biomarker potential has been proved by multiple studies [ 16 , 17 ]. In particular, circRNAs are generally proven to intervene in tumor stemness, migration, invasion, and metastasis [ 18 ]; for instance, they are involved in the activation of the epithelial–mesenchymal transition (EMT) process via the WNT/β-catenin signaling pathway, affecting directly the tumor progression [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding malignancy, miRNA-targeted therapy consists of inhibition of oncomiRs and upregulation of tumor-suppressor miRNAs. Inhibition of oncogenic miRNAs can be achieved by antagomiRs, which are antisense miRNA molecules, or by miRNA-sponges (e.g., circular RNAs [ 130 ]) that are molecules that act as competing endogenous RNAs and thus are able to bind the miRNA and prevent it from binding to the target mRNA. Tumor-suppressor miRNAs can be therapeutically replaced by using viral and non-viral vectors and miRNA mimics [ 21 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…However, similar to miRNA sponging, the low circRNA abundance may be challenging for them to affect protein binding significantly [ 70 ]. Regarding colorectal cancer, Karousi et al, 2020 [ 71 ] reported two novel circRNAs for both of which various protein-binding sites were detected, and many RBPs were predicted in silico to bind them. Among selected RBPs with more than five binding sites were serine and arginine-rich splicing factors (SRSF), FUS RNA-binding protein, heterogeneous nuclear ribonucleoprotein H1 (HNRNPH1), and others.…”
Section: Function and Properties Of Circular Rnasmentioning
confidence: 99%